2017
DOI: 10.5694/mja17.00457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of irritable bowel syndrome: a guide for the generalist

Abstract: Irritable bowel syndrome (IBS) and other functional gastrointestinal disorders (FGIDs) are so prevalent they cannot reasonably have their diagnoses and management based within specialty care. However, delayed diagnosis, lengthy wait times for specialist review, overinvestigation and lack of clear diagnostic communication are common. The intrusive symptoms of IBS and other FGIDs impair patient functioning and reduce quality of life, and come with significant costs to individual patients and the health care syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…By excluding organic GID, findings of non‐elevated FC levels also enable early and reliable diagnosis of a functional GID by general practitioners without gastroenterology referral or further testing. Confident diagnosis of a functional GID in primary care is likely to improve patient acceptance of their diagnosis and their uptake of effective management …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By excluding organic GID, findings of non‐elevated FC levels also enable early and reliable diagnosis of a functional GID by general practitioners without gastroenterology referral or further testing. Confident diagnosis of a functional GID in primary care is likely to improve patient acceptance of their diagnosis and their uptake of effective management …”
Section: Discussionmentioning
confidence: 99%
“…Confident diagnosis of a functional GID in primary care is likely to improve patient acceptance of their diagnosis and their uptake of effective management. 5 Accurate diagnosis of a functional GID reduces the number of referrals for more expensive and invasive investigations, including colonoscopy. An audit of colonoscopies in an Australian hospital found that 12% were for patients with functional gastrointestinal symptoms; further, 79% of patients seen in a public hospital who were diagnosed with a functional GID had undergone an endoscopic procedure, at an overall cost (including indirect costs) of $187 million, with an additional $2.4 million per year in emergency department presentations and hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations